The Prostate Problem You Can’t Put Your Finger on the Normal Way: A Case of Perineal Prostate Cancer Post Transperineal Prostate Biopsy - Kevin Yinkit Zhuo; James Kovacic; Amanda Chung; Thomas Eade; Venu Chalasani (Société Internationale d’Urologie Journal, 2023)
None.